Reactive oxygen species and antioxidant defense in human gastrointestinal diseases - Patlevič, Peter; Vašková, Janka; Švorc, Pavol; Vaško, Ladislav; Švorc, Pavol (Integrative medicine research, 2016)
Crohn's disease and ulcerative colitis, known together as inflammatory bowel diseases (IBDs), and celiac disease are the most common disorders affecting not only adults but also children. Both IBDs and celiac disease are associated with oxidative stress, which may play a significant role in their etiologies. Reactive oxygen species (ROS) such as superoxide radicals (O2•-), hydroxyl radicals (•OH), hydrogen peroxide (H2O2), and singlet oxygen (1O2) are responsible for cell death via oxidation of DNA, proteins, lipids, and almost any other cellular constituent. To protect biological systems from free radical toxicity, several cellular antioxidant defense mechanisms exist to regulate the production of ROS, including enzymatic and nonenzymatic pathways. Superoxide dismutase catalyzes the dismutation of O2•- to H2O2 and oxygen. The glutathione redox cycle involves two enzymes: glutathione peroxidase, which uses glutathione to reduce organic peroxides and H2O2; and glutathione reductase, which reduces the oxidized form of glutathione with concomitant oxidation of nicotinamide adenine dinucleotide phosphate. In addition to this cycle, GSH can react directly with free radicals. Studies into the effects of free radicals and antioxidant status in patients with IBDs and celiac disease are scarce, especially in pediatric patients. It is therefore very necessary to conduct additional research studies to confirm previous data about ROS status and antioxidant activities in patients with IBDs and celiac disease, especially in children.
Keywords: Crohn's disease; radicals; pediatric patients; antioxidant enzymes; inflammatory bowel diseases